Pectoralis major myocutaneous island flap for reconstruction of head and neck defects - Hajgude, Varsha; Chawada, Meghraj J. (International Surgery Journal, 2016)
Background:Pectoralis major myocutaneous island flap for reconstruction has been used since many decades with success. There is need to evaluate the efficacy of pectoralis major myocutaneous island flap for reconstruction in head and neck surgeries. The objective of the study was to study reliability and usefulness of pectoralis major myocutaneous flap. Methods: This study was carried out for a period of two years at T. N. M. College and Nair Hospital, Mumbai. During this period 12 cases were treated and evaluated. Institutional ethics committee permission was taken. Individual patient consent was obtained. History and clinical examination was carried out as per the protocol. In all cases routine investigations as well as additional investigations as per the case were done. Pectoralis major myocutaneous island flap (PMMC) was used for primary and secondary procedures. Results:Age of patients ranged from 36-70 years. Majority of patients were between 51-70 years of age. In this study, males outnumbered females. The male to female ratio was 2:1. In the majority of cases, single paddle pectoralis major myocutaneous flap was used, whereas double paddle was used in only 2 cases. Donor site was sutured primarily in 8 cases. Split thickness skin grafting was done in 4 cases for donor site of D. P. flap. Superficial necrosis of skin Island was seen in one case. 50% of the patients did not have any complications. In five cases of cheek defect reconstruction, mouth opening was 2 finger breadths. There was no difficulty for swallowing of solids and liquids in 4 cases of pharyngocutaneous fistulae. Conclusions:Pectoralis major myocutaneous island flap for reconstruction of head and neck defects was found to be very effective. Post-operative complications were rare.